2022
DOI: 10.1111/cid.13169
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term impact of patients' compliance to peri‐implant maintenance therapy on the incidence of peri‐implant diseases: An 11‐year prospective follow‐up clinical study

Abstract: Objective: To prospectively evaluate the incidence of peri-implant diseases and the associated risk factors during 11 years of peri-implant maintenance therapy (PIMT). Material and Methods: A sample of 80 partially edentulous individuals rehabilitated with dental implants was invited to participate in a PIMT program (T1-prior to entering the PIMT program). After 11 years, 51 individuals remained regularly or irregularly adherent to PIMT (T2-last recall after 11 years) and were classified as regular (RC; n = 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 73 publications
2
7
0
4
Order By: Relevance
“…The EC presented a higher peri‐implantitis rate (17%) compared with RC (4%), and a 4.25× higher probability of being diagnosed with peri‐implantitis. Recently, Costa et al., in an 11‐year longitudinal study, demonstrated that EC (37%) are significantly more prone to develop peri‐implantitis when compared to RC (11%) 25 . Hence, our findings are consistent with previous observations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The EC presented a higher peri‐implantitis rate (17%) compared with RC (4%), and a 4.25× higher probability of being diagnosed with peri‐implantitis. Recently, Costa et al., in an 11‐year longitudinal study, demonstrated that EC (37%) are significantly more prone to develop peri‐implantitis when compared to RC (11%) 25 . Hence, our findings are consistent with previous observations.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Costa et al, in an 11-year longitudinal study, demonstrated that EC (37%) are significantly more prone to develop peri-implantitis when compared to RC (11%). 25 Hence, our findings are consistent with previous observations. In fact, the present study showed EC to be 4.5× more exposed to peri-implantitis compared to RC.…”
Section: Agreements and Disagreements With Previous Studiessupporting
confidence: 94%
“…Diversos fatores e indicadores de risco são relatados na literatura, sendo o tabagismo e diabetes universalmente aceitos. Ainda existem controvérsias sobre as evidências relacionadas a síndrome metabólica, doença cardiovascular aterosclerótica, obesidade e doenças periimplantares (WANDA et al, 2019;ALHAKEEM, 2022;COSTA et al, 2022).…”
Section: Discussionunclassified
“…A adesão do paciente a um programa de terapia de manutenção e suporte é um fator de risco importante para manter a saúde do implante e está diretamente relacionada ao fator mais discutido como desencadeador da doença que é o acúmulo de biofilme. A falta de profilaxia regular resultou em aumento do risco de desenvolvimento de peri-implantite, segundo trabalhos recentes (COSTA et al, 2022;ATIEH et al, 2022).…”
Section: Discussionunclassified
See 1 more Smart Citation